Body composition of Thin-Tailed Sheep fed with Carica seed supplementation (Carica pubescens) - Satrio, Adi Rahman; Idayanti, Rahma Wulan; Adiwinarti, Retno; Purbowati, Endang; Purnomoadi, Agung (Politeknik Negeri Jember, 2025)
The evaluation of Carica seed supplementation in feed was carried out to assess its effect on sheep body composition such as water, fat, and protein, using the urea space method which is one method of determining the body composition of livestock without cutting. The study involved 15 male thin-tailed sheep aged 3 months with an average initial body weight of 10.68±1.28 kg, using a completely randomized design (CRD) with three treatments: 5% (T1), 12.5% (T2), and 20% (T3) carica seed supplementation, with five replicates each. The observed parameters included feed intake, daily weight gain, as well as water, fat, and protein content in the body. ANOVA analysis at a 5% significance level revealed that different concentrations of Carica seed significantly affected (P<0.05) crude protein intake, daily weight gain, and body protein composition at week 11. The sheep in the T3 treatment showed the crude protein consumption and daily body weight gain as well as a significant increase in body protein composition compared to the other treatments. Overall, Carica seed supplementation led to a significant increase in body protein content, while having no significant effect on body fat and water composition.